Analisis Pemahaman Konsep Matematika pada Materi Operasi Bilangan Bulat di SMP Negeri 4 Gorontalo - Novrianus Christian Yanala; Hamzah B Uno; Abas Kaluku (Department of Mathematics, Universitas Negeri Gorontalo, 2021)
This research is a qualitative approach to analyze the understanding of concepts in the material of integer operations. The research was conducted at SMP Negeri 4 Gorontalo involving 25 students as the object of research. This is a descriptive study with indicators used to describe students’ understanding of mathematical concepts, among others (1) Presenting a concept in various forms of mathematical representation, (2) Restating a Concept, (3) classifying objects according to certain properties (according to the concept), (4) Applying the problem-solving concept or algorithm. Furthermore, interviews were conducted to deepen information about students’ understanding of mathematical concepts. The analysis of the results showed that students’ understanding of mathematical concepts on integer operations material was classified as moderate, which was indicated by the ability of students who only met some indicators of understanding the measured mathematical concepts.